Is More Always Better? An Empirical Investigation of the CAPM and the Fama-French Three-factor Model in Indonesia - Sutrisno, B; Nasri, R (KnE Social Sciences, 2018)
This study investigates the performance of the CAPM and the Fama-French threefactor model in Indonesia. This research employs time-series regression with monthly data from 2005 to 2015. The results reveal that the Fama-French three-factor model performs better than the CAPM in describing the excess return of stock portfolios in Indonesia. This result is robust to the equally-weighted method and the impact of the global financial crisis. Although the Fama-French three-factor model is superior to the CAPM, the results indicate that there are other factors to consider in determining asset pricing models that better capture stock return variations in the Indonesian stock market. This research implies that the investors should consider Fama-French factors when making their investment decisions. Furthermore, the investors should evaluate another factor impact the average returns. Keywords: Asset pricing, CAPM, Three-factor model, Size factor, Book-to-market factor, JEL Code: G12